(untitled) - Carey, Patrick (Australia, 2006)
Part of the New Perspectives Series, this text teaches students HTML and XHTML using a simple text editor to create basic to complex Web sites. Advanced tutorials on DHTML help students to further their skills by learning and applying DHTML to make interactive features such as animated text, image rollovers, menus, and expandable outlines.
Keywords: HTML (Document markup language),XHTML (Document markup language),Web sites,HTML ( Ngôn ngữ đánh dấu tài liệu),XHTML (Ngôn ngữ đánh dấu tài liệu),Trang Web; Design,Thiết kế